Didecyl dimethyl ammonium chloride as a highly efficient corrosion inhibitor for carbon steel in hydrochloric acid solution. Issue 1 (25th October 2021) - Wei, Xiaojing; Wang, Jue; Shi, Xin; Zhou, Feng; Gao, Duolong; Wen, Xiaohu; Zhong, Xiankang
Abstract : Purpose: This paper aims to discover a highly efficient corrosion inhibitor for 45# steel in hydrochloric acid solution and reveal the mechanism of inhibitors. Design/methodology/approach: In this paper, electrochemical measurements, weight loss measurements, surface characterization and theoretical calculation are used to evaluate the inhibition performance and reveal the mechanism of inhibitors. Findings: Results show that didecyl dimethyl ammonium chloride (DDAC), especially in combination with dodecane phenol plyoxyethylene, could provide a good protection performance for the carbon steel in hydrochloric acid. The N atoms and long alkyl chains in DDAC molecular structure play the vital role. Originality/value: Usually, DDAC is used as the compound chemical disinfectant in oilfield sterilization, medicine and health. However, to the best of the authors' knowledge, no study has shown that it can mitigate the corrosion of carbon steels in HCl solution.